Geotechnical characteristics and mitigation strategies for loess subgrades in the Ili Valley, China - Yinuo Feng; Zheng Lu; Yang Zhao; Wanxin Mo; Zhihui Ze; Yuanbiao Li (European Journal of Environmental and Civil Engineering, 2026)

Deguelin suppresses Nalm6 leukemia cell proliferation through lactate accumulation and ATP depletion - Xingyan Luo; Kaiyu Feng; Ketian Zhao; Ting Zhang; Juncheng Qiu; Huijie Guo; Yantang Wang; Shuxia Yang; Chunfen Mo; Yang Liu (Molecular Biology Reports, 2026)

Intrauterine exposure to HBsAg attenuates the immune response to hepatitis B vaccine via the miR-155-5p/MyD88 axis of DCs in mouse pups - Xufeng Cui; Jia Lian; Yangle Sun; Xiaosheng Zhang; Bihong Ke; Xinyuan Mo; Ying Zhang; Tian Yao; Yandi Li; Linying gao; Keke wang; Suping Wang; et al. (Medical Microbiology and Immunology, 2026)

Targeted emission controls for ozone pollution mitigation based on mesoscale weather pattern classifications in China’s Pearl River Delta region - Aoxing Zhang; Jiongkai Chen; Huiran Feng; Wei Tao; Jiajia Mo; Wenlu Wu; Jianfeng Guo; Tianle Sun; Long Yun; Min Yan; Xiaolin Wang; Tzung-May Fu (ENGINEERING Environment, 2026)

Genesis of high-grade uranium mineralization in sandstone-hosted uranium deposits in the northern Sichuan Basin - Zongbo Zhang; Zhengqi Xu; Minghui Yin; Qiwei Feng; Banghong Mo; Qiushuang Fan; Peng Ning; Taosheng Sun; Jincheng He (Ore and Energy Resource Geology, 2026)

Combined activated carbon/ultrafiltration treatment for reuse of discharged water from sedimentation tanks in drinking water treatment plants - Zhongheng Huang; Feng Zhang; Yanmei Mo; Yueqin He; Jinrong Lv; Huiyu Dong; Qian Xu; Kaisheng Diao; Bernard A. Goodman; Suni Liu; Shaogang Liu (Journal of Water Process Engineering, 2026)

Selective separation of heavy rare earth elements using a novel silane-grafted aminomethylphosphonate D152 cation-exchange resin - Mixuan Huan; Wenhan Sun; Zezuo Jiang; Chunlin He; Xinpeng Wang; Huawu Mo; Jinpeng Feng; Shaojian Ma (Hydrometallurgy, 2026)

Seed Germination in Red Mud: Roles of Plant Traits and Metal Availability - Jian-Rui Wang; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo; Rui-Xia Ma; Jing-Jing Feng (Water, Air, & Soil Pollution, 2026)

Low root temperature at flowering reduces rice yield by impairing photosynthetic assimilate partitioning and antioxidant defense more than low canopy temperature and drought in different rice genotypes - Qiqi Xiao; Xiaotong He; Jiemei Peng; Xiaolong Feng; Jinxi Zheng; Zhaowen Mo (Plant Science, 2026)

Responses of aerosol optical properties and direct radiative effects to rapid shifts in anthropogenic emissions in the sichuan basin - Fengjun Shen; Jie Sun; Guiying You; Jiaxin Wei; Xinlei Lv; Qiqi Mo; Tong Liu; Miao Feng; Yanyi Feng; Shaodong Xie; Gang Zhao; Min Hu (Environmental Pollution, 2026)

Breaking lignin barrier for co-producing hydrochar and crop salinity stress biostimulants - Fangfang Wu; Qianyi Deng; Wenqing Chen; Xueyi Zhong; Yanying He; Yixian Feng; Nijia Chen; Kai Qiu; Dingli Chen; Xueying Mo; Siyuan Chen; Long Chen; et al. (Chemical Engineering Journal, 2026)

Evolution and formation pathways of volatiles during co-pyrolysis process of coal and various polymers based on ReaxFF MD simulation and in-situ Py-TOF-MS - Wei Feng; Xiaodong Chen; Jin Bai; Mo Zheng; Jinjun Guo; Congbin Jiang; Xianxian Zhang; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2026)

A numerical study of bubble departure characteristics and the dominant mechanism under periodic external vibration - Chunxiao Zhu; Yi Feng; Tianyi Gao; Zhengyu Mo; Min Du; Jiaxin Zheng; Xin Xu; Qinyi Zhang; Licheng Sun (Annals of Nuclear Energy, 2026)

Pip5k1α defines a mandible-specific phosphoinositide signaling axis in mice - Yiting Tang; Yao Feng; Yijia Shi; Bo Zhou; Jingjing Zhang; Songlin Wang; Mo Chen (Science China Life Sciences, 2026)

The quantitative assessment of stormwater regulation services under urbanized landscape pattern employed SCS model in the whole Nanning, China - Yunchuan Yang; Minhui Feng; Guangqiong Bi; Liping Liao; Jiaoyin Wei; Yaqian Tang; Yuhong Huang; Chongxun Mo; Guikai Sun; Xungui Li (Environment, Development and Sustainability, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Composition characteristics of the distillation waste residue from coal gasification crude phenol and pyrolysis product distribution of the corresponding residue - Jing Zhou; Bao-Kun Shi; Qing-He Ma; Ya-Ya Ma; Jie Yuan; Wen-Long Mo; Feng-Jun Ding; Bing Hu; Xing Fan; Xian-Yong Wei; Hai-Bao Huang (Fuel, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Decoding the neural mechanisms of salty peptide perception via electroencephalography and machine learning - Xuchao Feng; Hongbo Li; Quanyu Dai; Na Li; Lili Zhao; Zhenbin Liu; Jiayi Zhang; Haizhen Mo (Food Chemistry, 2026)

Enhancing Daily Runoff Prediction Accuracy with the Coupled KAN-LSTM Model and a Dynamic Postprocessing Module - Chongxun Mo; Tao Feng; Keke Huang; Zhiwei Yan; Zihan Lin; Haiyang Wang; Jiameng Xu; Yuyi Zhong; Gang Tang; Yi Huang (Water Resources Management, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Ultrafast degradation of mineral processing collector via magnetic Fe3O4/graphene oxide activating peroxydisulfate: Performance and mechanism - Zequan Lin; Wei Mo; Yuxin Feng; Junjie Wu; Xiujuan Su; Jinlin Yang; Yuhua Huang; Jinpeng Feng; Shaojian Ma (Journal of Environmental Chemical Engineering, 2026)

Interpretable deep learning method integrating spatial self-attention for generating bias-corrected high-resolution GFS precipitation forecasts - Haiyang Wang; Shufeng Lai; Chongxun Mo; Tao Feng; Changhao Jiang; Na Li (Atmospheric Research, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

A novel UV-assisted modification for fabricating wrinkled ligninsulfonate nanofiltration membranes with high flux and antibacterial properties - Guizhen Feng; Kailin Mo; Zhicheng Cui; Chaoran Fan; Yuntao Zou; Ju Rao; Zunquan Huang (Journal of Cleaner Production, 2026)

Silver-doped ZnMn bimetallic oxide nanostructures for enhanced photocatalytic degradation of iron(III) cyanide complexes (Fe-CNs) cyanide complexes via synergistic effects of plasmonic activation and dual-metal redox catalysis - Jing Feng; Jingyu He; Anyang Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Shaojian Ma (Journal of Environmental Chemical Engineering, 2026)

Bioactive biphasic textile scaffold for spatiotemporal regulation of inflammation and osteogenesis in enthesis healing during anterior cruciate ligament reconstruction - Meilin Song; Yanran Du; Haohan Li; Jiankun Feng; Xianchao Li; Yakun Huang; Yu-Qing Zhao; Chengbo Li; Huanhuan Yan; Dongsheng Li; Xiumei Mo; Guige Hou; et al. (Chemical Engineering Journal, 2026)

Amorphous Fe–Al binary hydroxides for enhanced Arsenic removal: Mechanistic role of stoichiometry and synergistic adsorption - Maulidiah Nani Lailil Islahah; Wei Mo; Yang Yang; Shaojian Ma; Jinlin Yang; Jinpeng Feng; Xiujuan Su (Process Safety and Environmental Protection, 2026)

Global governance priorities derived from SDG spatiotemporal dynamics and causal interactions - Yizhong Huan; Linjiang Ji; Yiming Su; Feng Kong; Yang Lan; Zhaohui Feng; Siyu Wang; Tao Liang; Mingyuan Wang; Pengpeng Mo; Jian Hu; Lingqing Wang; et al. (Gondwana Research, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

Quantifying the impact of nanoplastics and natural particles on copper accumulation and distribution in zebrafish: Coupling in vivo tests with toxicokinetic modeling - Xiaorong Luo; Xue Yu; Chenglong Han; Ning Gao; Xunqiang Mo; Jianfeng Feng; Xueqiang Lu (Environmental Pollution, 2026)

Linking microbial life history strategy to carbon use efficiency under changing substrate and nutrient conditions - Gang Huang; Yan-feng Cao; Meng-hui Dong; Mo Bahram; Yan-gui Su (CATENA, 2026)

A probabilistic-based entrainment erosion model combined with the Eulerian-Lagrangian method to simulate snow distribution - Zhenkun Du; Qingwen Zhang; Guolong Zhang; Huamei Mo; Zhongshan Zhang; Feng Fan (Building and Environment, 2026)

Mitochondria beyond boundaries: from cellular powerhouses to intercellular messengers in health and disease - Haixia Zhuang; Wenxin Mo; Jianming Xie; Tingting Zhang; Kailun Qiu; Weinan Wu; Wanyue Tan; Xiaoyi Jiang; Xiusheng Chen; Yongquan Hu; Huansen Huang; Hao Liu; et al. (Science China Life Sciences, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Single-cell immune atlas of mouse testes unveils metabolic reprogramming of FOLR2 + macrophages in orchestrating testicular immunity during aging - Xinyu Li; Min Zhang; Ani Chi; Jiahui Mo; Xiaofeng Tan; Hongde Chen; Chunhua Deng; Xiangzhou Sun; Xin Feng; Zhihong Chen (GeroScience, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

Hierarchically structured fiber scaffold incorporating functionalized microspheres for sustained drug release and treatment of infected wounds - Hao Feng; Gonghao Zhang; Sidong Zhang; Lu Han; Zhengchao Yuan; Xiao Yu; Shuqi Lou; Yunhan Ji; Muhammad Shafiq; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Xiumei Mo; et al. (Chemical Engineering Journal, 2026)

Development and application of a new simple algorithm for stochastic modeling of daily ground snow loads: A case study in Northeastern China - Huamei Mo; Yuanyuan Li; H.P. Hong; Guolong Zhang; Qingwen Zhang; Feng Fan (Cold Regions Science and Technology, 2026)

Carbon-regulated MnxOy catalysts from Mn-MOF-74: Synergistic effects on glucose oxidation to formic acid - Hongrui Guo; Chengjie Sun; Mo Qiu; Hejuan Wu; Zhihui Ma; Jirui Yang; Feng Shen (Biomass and Bioenergy, 2026)

Synergistic Neuroprotection of Combined Shenmai and Hypothermia in Cerebral Ischemia–Reperfusion Injury via ERK-Dependent Anti-inflammatory Effects - Yuan Wang; Hangui Ren; Yufei Qiu; Rongchen Dai; Mengfan Liu; Shiting Mo; Yibo Zhang; Wang Fu; Qianqian Bi; Yongpeng Wang; Yunuo Zhou; Zhichao Xi; et al. (Molecular Neurobiology, 2026)

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

Endophytic Bacillus toyonensis D-6 via producing antifungal volatile organic compounds effectively controls green grape postharvest diseases - Lijun Ling; Wenyue Zhang; Rui Yue; Yijuan Jiang; Fanjin Kong; Rongxiu Mo; Lijun Feng; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Enhanced water flux and antifouling of a positively charged MoS2/PEI nanofiltration membrane through TA functionalization for effective dye desalination - Guizhen Feng; Kailin Mo; Jun Chen; Huomei Zhang; Zhicheng Cui; Chaoran Fan; Yuntao Zou (Journal of Environmental Chemical Engineering, 2025)

Fe/Mn-MOF@PDA sponges: A hydrolytically stable and facilely recoverable material for arsenic removal through polydopamine-mediated homogeneous MOF immobilization - Wei Mo; Xin Liu; Yang Yang; Chengcheng Wei; Yuhua Huang; Jinlin Yang; Aoping He; Jingni Liao; Xiujuan Su; Jingpeng Feng; Shaojian Ma (Journal of Environmental Chemical Engineering, 2025)

Prion-inhibition-like protein (PiP) governs Aspergillus flavus spore dormancy under postharvest drying stress: A novel target for aflatoxin mitigation in grain storage systems - Chen Xuan; Feng Chengyuan; Liu Mengdan; Meng Ruitong; Xu Dan; Yao Lishan; Li Hongbo; Mo Haizhen; Hu Liangbin; Zhou Xiaohui (Food Microbiology, 2025)

Probabilistic analysis of suction caisson foundations for offshore wind turbines under lateral loading considering spatial variability of the critical state stress ratio via SANISAND-MS model - Hongfen Zhao; Jinbiao Mo; Yu Feng (Computers and Geotechnics, 2025)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Identification of lncRNA expression profiles associated with ovarian development and ageing process in mice - Siyuan Chen; Zixue Zhou; Jitong Mo; Xi Yang; Yuncheng Pan; Renbin Liu; Muhammed Boye Jallow; Feng Zhang; Yanhua Wu (Journal of Applied Genetics, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Effect of microplastics on antibiotic resistome risk in composting - Yiwen Yang; Xiaoyue Tang; Pengfei Zhang; Chunhao Mo; Feng Huang; Zhiguo Wen (Environmental Research, 2025)

Fermentation-weakened BF/PBAT film facilitates Tenebrio molitor consumption: Prolonged larval longevity maximizes PBAT biodegradation and soil metabolic activity - Shengqi Zhan; Huaming Zheng; Shusen Mo; Feng You; Wingho Lai; Qun Yi (Chemical Engineering Journal, 2025)

Calcium-doped barium titanate (Ba0.8Ca0.2TiO3)-modified piezo-photocatalytic self-cleaning ceramic composite membrane for oily wastewater remediation - Lei Zhang; Weigui Fu; Qianqian Mo; Min Feng; Meixiu Sun; Yiping Zhao; Li Chen (Chemical Engineering Journal, 2025)

Pyrite-activated peracetic acid for enhanced sludge dewaterability: Molecular insights into reactive species generation and interfacial interaction mechanisms - Zhihua Mo; Jiapeng Zhong; Lanrong Zhao; Yuqiong Li; Rongyue Wang; Pengzhan Sha; Jialin Liang; Shuiyu Sun; Wei Guo; Jinxi Feng; Kengbo Ding; Chuanhao Li (Chemical Engineering Journal, 2025)

Study on the characteristics of vibration acoustic signals and rupture grading for reactor pipeline leaks - Xinyu Zhao; Zhuorun Zhang; Xiangpeng Du; Yu Wang; Jinchuan Yang; Zhangjun Feng; Ruiyang Zhong; Chuang Han; Jiaxin Mo; Jinlong Wan; Zhida Yang (Annals of Nuclear Energy, 2025)

Efficient separation of impurities from pyrolusite and the enhancement of its products for improving the performance of lithium-ion batteries - Riran Zang; Houyang Chen; Shuxian Shi; Man mo; Dawei Lan; Guangliang Zhang; Yangxian Huang; Kunsong Hu; Xinghua Liang; Lingxiao Lan; Yong Yang; Junji Li; et al. (Chemosphere, 2025)

Crystallinity and energy level modulation in organic mixed ion-electron conductors: facilitating high-performance OECTs and diverse applications - Ting Wang; Songlin Mo; Ziyi Du; Shaodan Cai; Chao Deng; Wang Feng; Qilin Peng; Hongxiang Li; Jianhua Chen (Chemical Engineering Journal, 2025)

CFD investigations into snow loads on tandem-arranged gabled-roofed buildings under mutual interferences - Guolong Zhang; Qingwen Zhang; Huamei Mo; Dong Guo; Xudong Zhi; Jinzhi Wu; Feng Fan (Cold Regions Science and Technology, 2025)

Retraction Note: Enhancing sensitivity to oxaliplatin in tongue squamous cell carcinoma: mechanistic insights and therapeutic potential of DHA combination therapy - Hailan Mo; Hongyan Fang; Lifeng Jia; Shitong Zhou; Menglong Feng; Xiaolu Wu; Wei Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

High co-infection burden and ICU-specific pathogen profiles in pediatric Candida albicans respiratory infections: a large-scale tNGS analysis - Ya Huang; Huideng Zhou; Jiangyang Zhao; Lishai Mo; Junming Lu; Guangbing Liu; Shuo Zhang; Yanhua Feng; Wenting Tang; Qiang Huang; Yan Chen; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Bacillus thuringiensis G-5 efficiently suppresses Codonopsis pilosula postharvest diseases by generating antifungal volatile organic compounds - Rongxiu Mo; Lijun Feng; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Lijun Ling (Antonie van Leeuwenhoek, 2025)

Analysis on Phase Polarity of Mandrel Fiber-Optic Vector Hydrophones Based on Phase Generated Carrier Technique - Yatao Li; Jianfei Wang; Rui Liang; Jingjing Feng; Mo Chen; Jiaze Zhao; Zhou Meng (Journal of Marine Science and Engineering, 2025)
In ocean engineering, the demand for fiber-optic vector hydrophones (FOVHs) is increasing. The performance of a FOVH depends on phase consistency between its pressure and acceleration channels, which should match the acoustic field’s properties. Phase polarity, which refers to the alignment of the output signal with the acoustic field direction, is critical. Incorrect phase polarity during sensor assembly can disrupt phase consistency and invalidate directional measurements. This study investigates phase polarity in mandrel FOVHs that use the Phase Generated Carrier (PGC) technique. We develop a theoretical model combining the PGC algorithm with elastic mechanics to analyze the response of acoustic signals. Our model shows that correct demodulated signal polarity requires a specific physical setup: the pressure sensor’s long arm should be on the inner mandrel and the short arm on the outer, while the accelerometer’s positive axis should follow the vector from the long to its short arm. These results are validated through standing wave tube experiments and lake tests. This research provides practical guidelines for the installation and calibration of FOVHs, ensuring phase consistency in underwater acoustic sensing.

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Modulating polyamide nanofiltration membrane with silica nanoparticles as aqueous-phase additive for a significant enhancement in surface water treatment - Guizhen Feng; Zhicheng Cui; Xiaojie Hu; Kailin Mo; Huomei Zhang; Jun Chen (Journal of Water Process Engineering, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Multiscale periodic macroporous tantalum oxide: Structural engineering for enhanced and stable photocatalytic hydrogen evolution - Chunmei Wu; Linsen Peng; Yihan Tong; Manxing Mo; Feng Liu; Rongbin Zhang; Junchao Wei; Aiyu Yang; Xuewen Wang (Chemical Engineering Journal, 2025)

Long-Term Fertilization Effects on Forms and Availability of Phosphorus Associated with Humic Substance Fractions in a Mollisol in Northeast China - Jinjing Zhang; Yuanhong Sun; Yuhan Yuan; Hongbin Ma; Yanhui Feng; Zhihan Zhang; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Longitudinal transport of net suspended sediment in the river-dominated Modaomen Estuary of the Pearl River: Effects of river, tide, and mouth bar - Xinran Li; Feng Liu; Hao Zou; Chao Tan; Jie Huang; Sihao Mo; Haiwei Li; Rongyao Xie; Heng Wang (Marine Geology, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced hemicellulose retention in lignocellulosic biomass fractionation with ethylene glycol-regulated deep eutectic solvent - Siwei Chen; Fukuan Li; Zhihui Ma; Haixin Guo; Jirui Yang; Mo Qiu; Feng Shen (Bioresource Technology, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Encephalomyocarditis virus non-structural protein 2C induces the degradation of NDP52 autophagy protein to promote its own survival - Rongqian Mo; Rongrong Cheng; Pingan Dong; Tingting Ma; Yaxin Zhang; Jingying Xie; Shasha Li; Huixia Li; Adi Idris; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

6-Gingerol and 6-shogaol attenuate chemotherapy-induced nausea and vomiting via ameliorating mitochondrial dysfunction and pyroptosis through JNK/MFF signaling pathway - Yarong Zhai; Lei Feng; Ziyao Mo; Binbin Ye; Wan Liang; Ke Nie (Food Bioscience, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

Versatile fabrication of hydrogel coatings with shell powder as a key Ingredient - Feng Li; Jianwan Lin; Yongqi Li; Shijia Wu; Cha Wen; Mengting Mo; Linfeng Huang; Ning Qing; Zhenpin Lu; Xing Jiang; Liuyan Tang (Chemical Engineering Journal, 2025)

Clinical characteristics and co-infection analysis of influenza a virus in pediatric respiratory infections: a study based on tNGS technology - Chunyun Fu; Qiang Huang; Jiangyang Zhao; Lishai Mo; Wenting Tang; Junming Lu; Yili Zhang; Xiangjun Lu; Ya Huang; Yanhua Feng; Xuehua Hu; Yanqing Tang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Microwave-enhanced Fe/Al recovery from red mud: Mechanistic role of carbothermal reduction and alkali activation in mineral transformation - Yuhua Huang; Wei Mo; Jinpeng Feng; Chunyan He; Jinlin Yang; Shaojian Ma; Xiujuan Su (Process Safety and Environmental Protection, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Optimizing visible light absorption, exciton dissociation, and charge transfer through the interaction of donor-acceptor materials to enhance xanthate photodegradation - Anyang Huang; Jingyu He; Ciyuan Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Xiurong Li; Aoping He; Bingsuo Zou; et al. (Journal of Environmental Management, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Butyl xanthate photocatalytic degradation using a highly effective, stable organic solar active layer that attaches to various silicate substrates - Jingyu He; Anyang Huang; Zhengxian Pan; Menghao Zhang; Jinpeng Feng; Shaojian Ma; Ciyuan Huang; Jinlin Yang; Wei Mo; Xiujuan Su; Wenhan Sun; Dingzheng Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Preparation of copper mine tailings-based geopolymers as thermal storage functional backfill materials - Yuxiang Chen; Degao Xiao; Jianbiao Wei; Liwei Mo; Feng Rao; Lang Yang (Environmental Research, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Identifying a gene signature for age-related hearing loss through machine learning and revealing the effect of the CTSS on the mice cochlea - Xu Jiang; Jing Ke; Yiting Liu; Xiaoqin Luo; Menglong Feng; Hailan Mo; Wei Yuan (Biogerontology, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Microwave-assisted modification of magnetic Mg/Al/Fe-LDH hydrotalcite for efficient arsenic removal from water - Chunyan He; Wei Mo; Yang yang; Wei Guo; Yuhua Huang; Chang Yu; Xiujuan Su; Jinlin Yang; Jinpeng Feng; Aoping He; Shaojian Ma (Journal of Environmental Management, 2025)

Lactiplantibacillus plantarum T34 alleviates constipation by enhancing intestinal barrier and modulating gut homeostasis - Fei Shen; Huiting Zhu; Zhongyan Bao; Di Han; Juan Du; Minjie Zhao; Fengqin Feng; Guanghua He; Qiufen Mo (Food Bioscience, 2025)

RETRACTED ARTICLE: Enhancing sensitivity to oxaliplatin in tongue squamous cell carcinoma: mechanistic insights and therapeutic potential of DHA combination therapy - Hailan Mo; Hongyan Fang; Lifeng Jia; Shitong Zhou; Menglong Feng; Xiaolu Wu; Wei Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Clinical and prognostic insights into Chlamydia trachomatis in pediatric acute respiratory infections: evidence from targeted next-generation sequencing of 5,021 cases - Chunyun Fu; Huan Zhang; Xiangjun Lu; Yanhua Feng; Lishai Mo; Junming Lu; Huiping Huang; Qiang Huang; Cuihong Lu; Wenting Tang; Ruting Chen; Silin Jiang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Extraction of typical oyster pile columns in the Maowei Sea, Beibu Gulf, based on unmanned aerial vehicle laser point cloud orthophotos - Jinze Du; Meiqin Huang; Zhenjun Kang; Yichao Tian; Jin Tao; Qiang Zhang; Yutong Xie; Jinying Mo; LiYan Huang; Yusheng Feng (Frontiers in Marine Science, 2025)
Pile culture is a breeding method commonly used for oyster seedlings in the intertidal zone of southern China. Artificial visual interpretation serves as the primary monitoring approach for oyster seedling cultivation in marine areas. Manual visual interpretation is often time-consuming, inefficient, and does not provide spatially continuous information about the structure. Consequently, obtaining data on oyster pile columns and oyster seedling culture areas presents certain limitations. This study focuses on Shajing Town, Qinzhou City, Guangxi Zhuang Autonomous Region, China, as its research area. It utilizes multi-spectral image data from unmanned aerial vehicles (UAVs), light detection and ranging (LiDAR) point cloud technology, and deep learning algorithms to extract representative oyster pile columns in Maowei Sea within Beibu Gulf. By employing band features and texture indices extracted from UAV’s multi-spectral images as data sources and combining them with a classification and prediction model based on deep learning convolutional neural networks (CNN), we successfully extract the desired oyster pile columns. The results demonstrate that: 1) By comparing three machine learning models and integrating the LiDAR point cloud oyster pile column height model (OPCHM) into the S3 scenario, the convolutional neural network (CNN) attains an impressive overall classification accuracy (OA) of 96.54% and a Kappa coefficient of 0.9593, significantly enhancing and optimizing the CNN’s predictive accuracy for classification tasks; 2) In comparison with conventional machine learning algorithms, deep learning exhibits remarkable feature extraction capability.

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Crop yield and soil quality of soya bean-maize rotation in response to 8-year keep stubble with no tillage practices on the Northeast China - Weijian Zhang; Jingyi Feng; Xueyan Bai; Wanying He; Jixian Mo; Qiance Gao; Kunjie Wang; Siyu Gu (European Journal of Agronomy, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Research on controlling measures of snowdrifts around Arctic ground-based buildings through shape optimization - Qingwen Zhang; Guolong Zhang; Ruixiang Zheng; Huamei Mo; Xudong Zhi; Jinzhi Wu; Feng Fan (Cold Regions Science and Technology, 2025)

Role of nucleotide pair frequency and synonymous codon usage in the evolution of bovine viral diarrhea virus - Xili Feng; Zeyu Liu; Yongli Mo; Shubin Zhang; Xiao-Xia Ma (Archives of Virology, 2025)

Supplementation with L-kynurenine during in vitro maturation improves bovine oocytes developmental competence through its antioxidative action - Canqiang Lu; Yun Feng; Zhenhua Tang; Ruru Jia; Fan Xia; Tingzi Yu; Heng Wang; Hongfang Mo; Deshun Shi; Fenghua Lu (Theriogenology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Attachment and removal of porcine rotavirus (PRV) and Tulane virus (TV) on fresh and artificial phylloplanes of Romaine lettuce and Carmel spinach as affected by ultrasonication in combination with oxidant- or surfactant-based sanitizer(s) - Sindy Palma-Salgado; Kang-Mo Ku; John A. Juvik; Elbashir Araud; Thanh H. Nguyen; Hao Feng (International Journal of Food Microbiology, 2025)

The influence of different flavor peptides on brain perception via scalp electroencephalogram and development of a taste model - Hongbo Li; Xuchao Feng; Zhenbin Liu; Wenting Wang; Lufei Tian; Dan Xu; Bimal Chitrakar; Zhenkun Cui; Liangbin Hu; Haizhen Mo (Food Chemistry, 2025)

Probing the potential microbiota-mediated effects of sodium dehydroacetate on hyperphagia and inflammation in mice - Qiufen Mo; Fei Shen; Shengyue Ruan; Junhui Zhang; Minjie Zhao; Fengqin Feng; Tao Liu (Food Bioscience, 2025)

Hyaluronic acid-functionalized ruthenium photothermal nanoenzyme for enhancing osteosarcoma chemotherapy: Cascade targeting and bidirectional modulation of drug resistance - Weifeng Chen; Hao Feng; Yinyin Mo; Zhihui Pan; Shichen Ji; Hong Liang; Xing-Can Shen; Bang-Ping Jiang (Carbohydrate Polymers, 2025)

Fe/Mn-MOF-driven rapid arsenic decontamination: Mechanistic elucidation of adsorption processes and performance optimization - Yang Yang; Wei Mo; Chengcheng Wei; Maulidiah Nani Lailil Islahah; Yuhua Huang; Jinlin Yang; Jingpeng Feng; Xiujuan Su; Shaojian Ma (Journal of Water Process Engineering, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Combined application of organic and inorganic fertilizers sustained rice yields and N accumulation and decreased soil-canopy system NH3 emission - Bo Shang; Tongtong Tian; Yatong Mo; Han Zhang; Kun Zhang; Evgenios Agathokleous; Yang Ji; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2025)

Heavy metal contamination of vegetables in China: status, causes, and impacts - Jing-Jing Feng; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo (Environmental Science and Pollution Research, 2024)

Investigating the environmental dynamics of emerging pollutants in response to global climate change: Insights from bibliometrics-based visualization analysis - Bogui Pan; Hong Tian; Boyou Pan; Ting Zhong; Miao Xin; Jinhua Ding; Junyu Wei; Hong-Jia Huang; Jing-Qian Tang; Fengtao Zhang; Nai-Xian Feng; Ce-Hui Mo (Science of The Total Environment, 2024)

Multi-scale correlation reveals the evolution of socio-natural contributions to tropospheric HCHO over China from 2005 to 2022 - Hui Xia; Dakang Wang; Gonzalo González Abad; Xiankun Yang; Lei Zhu; Dongchuan Pu; Xu Feng; Aoxing Zhang; Zhaolong Song; Yongru Mo; Jinnian Wang (Science of The Total Environment, 2024)

Fe3O4@Mg/Al/Fe-LDH adsorption properties of As(V) and As(III) co-existing in water - Wei Mo; Chengcheng Wei; Chunyan He; Yang Yang; Maulidiah Nani Lailil Islahah; Xiujuan Su; Jinlin Yang; Yuhua Huang; Jinpeng Feng; Shaojian Ma (Journal of Water Process Engineering, 2024)

Polystyrene microplastics facilitate the chemical journey of phthalates through vegetable and aggravate phytotoxicity - Bogui Pan; Boyou Pan; Yiyuan Lu; Kunzheng Cai; Xiaoqiong Zhu; Li Huang; Lei Xiang; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Bacterial community succession and its correlation with the dynamics of flavor compound during processing of Enshi bacon - Yating Liu; Yao Xiao; Wu Feng; Zhongyan Mo (Food Bioscience, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Profile of miRNA expression in the hippocampus of epileptic mice and the prediction of potential therapeutic targets - Yafu Tan; Yongjia Yu; Haodong Niu; Chunxi Wang; Panlin Mo; Dongqiao Li; Qing Zhang; Daqin Feng; Chang Liu (Molecular Biology Reports, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Impaired inducibility of immune regulatory capacity of peripheral B cells of patients with recurrent pregnancy loss - Fei Ma; Xiaoyang Feng; Shiyu Feng; Jin Liu; Jia Li; Lihua Mo; Lingzhi Xu; Yulei Liu; Jiaman Wu; Pingchang Yang; Yan Ning (Immunologic Research, 2024)

Desertibaculum subflavum gen. nov., sp. nov., a novel member of the family Sneathiellaceae isolated from the Kumtag Desert soil - Chu-Ying Feng; Huan-Huan He; Shuai Li; Zhuo-Huan Zheng; Yi-Jun Mo; Wen-Hui Lian; Chun-Yan Lu; Dong-Ya Zhang; Wen-Jun Li; Lei Dong (Antonie van Leeuwenhoek, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

A multi-objective operation optimization method for dynamic control of reservoir water level in evolving flood season environments - Li Zhang; Zhong-kai Feng; Xin-ru Yao; Wen-jing Niu; Yong-qiang Wang; Li Mo (Journal of Hydrology, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Photocurrent-polarity-switching photoelectrochemical and electrochemical dual-mode sensing platform for the highly selective detection of trenbolone - Feng Jiang; Shanghua Liu; Mengxiao Mo; Xinyu Liu; Dongyu Han; Qing Liu; Yueyuan Li; Yueyun Li; Yaqi Li; Qin Wei (Chemical Engineering Journal, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Deep learning-based geological parameterization for history matching CO2 plume migration in complex aquifers - Li Feng; Shaoxing Mo; Alexander Y. Sun; Dexi Wang; Zhengmao Yang; Yuhan Chen; Haiou Wang; Jichun Wu; Xiaoqing Shi (Advances in Water Resources, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Alkali pretreatment-assisted catalytic pyrolysis of waste cellulose acetate for selective preparation of levoglucosenone - Shi-Yu Feng; Sheng Li; Wan-Zhao Huang; Qi Niu; Deng-Yu Chen; Zhi-Mo Fang; Li-Juan Gao; Kai Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

Comprehensive analysis reveals the differentiated influential mechanism of biodegradable and non-biodegradable microplastics on core microbial metabolisms and functional genes in an adsorption-biological coupling wastewater treatment system - Shengtao Liu; Zhu Liang; Xiaoyu Feng; Hujian Li; Mo Chen; Shu Gao; Yuxiang Lu; Chengyuan Su (Chemical Engineering Journal, 2024)

Dynamic fractionation of methane carbon isotope during mass transport in coal with bidisperse pore structures: Experiments, numerical modeling, and applications - Jun Wang; Feng Wang; Fangwen Chen; Shuangfang Lu; Yongzhou Li; Mo Chen; Yuan Wang; Chunhu Li; Yuxiang Zhang; Wenbiao Li (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Effects of heat stress on the feeding preference of yellow-feathered broilers and its possible mechanism - Xiajie Feng; Ziyuan Ye; Kailai Xie; Shuqing Zhu; Xin Wu; Zhonghua Sun; Xiaohua Feng; Yingfen Mo; Jingwen Liang; Gang Shu; Songbo Wang; Canjun Zhu; et al. (Journal of Thermal Biology, 2024)

Development of a facile one-pot synthesized fluorescent green polyesters as cooling water antiscalants for industrial application - Lijun Gao; Tianming Gao; Jiuying Feng; Shaohong Mo; Yanbei Guo; Pingping Guo; Shiyun Pan; Yuqing Cheng; Qian Yang (Desalination, 2024)

Ball billing induced highly dispersed nano-MgO in biochar for glucose isomerization at low temperatures - Siyu Xu; Haixin Guo; De Li; Hejuan Wu; Mo Qiu; Jirui Yang; Feng Shen (Bioresource Technology, 2024)

Efficient one-pot conversion of corncob to formic acid using bi-functional MnCeOx/Nb2O5 catalyst - Siyu Xu; Jirui Yang; Hejuan Wu; Haixin Guo; Mo Qiu; Xiao Zhang; Feng Shen (Biomass and Bioenergy, 2024)

Exploring the relationship between infectious agents and autoimmune diseases: a review - Zhihui Feng; Xueli Yang; Biao Zhang; Chune Mo; Chunhong Li; Xiayu Tian; Chong Zhang; Minglin Ou; Xianliang Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Root-zone regulation and longitudinal translocation cause intervarietal differences for phthalates accumulation in vegetables - Bogui Pan; Xiaoqiong Zhu; Li Huang; Kunzheng Cai; Yan-Wen Li; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Chemosphere, 2024)

Potential structure–function relationships of pectic polysaccharides from quinoa microgreens: Impact of various esterification degrees - Jie Li; Jing Feng; Xiao Luo; Mei-Mei Qu Mo; Wen-Bing Li; Jing-Wei Huang; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Research International, 2024)

Sulfated cellulose nanofibrils-based hydrogel moist-electric generator for energy harvesting - Jilong Mo; Xijun Wang; Xuejiao Lin; Xiao Feng; Changjing Qiu; Shenming Tao; Pinhong Chen; Kunkun Zhu; Haisong Qi (Chemical Engineering Journal, 2024)

Characteristic structures of liquid crystal monomers in EI-MS analysis and the potential application in suspect screening - Jing-Jing Feng; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo (Chemosphere, 2024)

Zinc improves the developmental ability of bovine in vitro fertilization embryos through its antioxidative action - Yun Feng; Xin Zhao; Ziyun Ruan; Zhengda Li; Hongfang Mo; Fenghua Lu; Deshun Shi (Theriogenology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

CO2 fluxes contrast between aquaculture ponds and mangrove forests and its implications for coastal wetland rehabilitation in Leizhou Peninsula, China - Ruikun Gou; Jianxiang Feng; Haichao Zhou; Tao Lang; Jiayu Zhao; Lidong Mo; Shanshan Song; Guanghui Lin (Agriculture, Ecosystems & Environment, 2024)

Decadal evolution of a sandy beach adjacent to a river mouth under natural drivers and human impacts - Gen Liu; Feng Cai; Hongshuai Qi; Jianhui Liu; Chao Cao; Shaohua Zhao; Yanyu He; Jun Zhu; Chao Yin; Wenyuan Mo (Frontiers in Marine Science, 2024)
As escalating environmental pressures threaten the world’s beaches, understanding the driving factors influencing their geomorphological changes is of critical global importance. This study focuses on the morphological changes of Sigeng beach adjacent to Changhua River Mouth in Hainan Island, China through decadal monitoring of shoreline and profile topography and tries to illuminate the natural and anthropogenic factors that drove geomorphological changes. The results showed that Sigeng beach undergone significant changes between 2008 and 2024, with notable accretion at the northernmost and southernmost and general erosion at other sections. The shoreline change rates ranged between -18.4 m/yr and 13.0 m/yr, with the average rate of -1.9 m/yr, indicating overall erosion. The net longshore sediment transport (LST) rates along Sigeng beach was estimated through the combination of the cross-shore (profile) and longshore (shoreline) changes. The overall direction of net LST along the beach were southward, except for the northern section where the direction was northward due to the diffraction of NE waves by the long sand spit at the northernmost. The net LST rates at each profile varied from 0.8×10 4 m 3 /yr to 3.5×10 4 m 3 /yr. The main factors controlling Sigeng beach evolution, including seasonal wave action and reduction in fluvial sediment load, followed by sand spit and coastal structures, typhoon events, aeolian transport, and sea level rise, were discussed. Subsequently, adaptive protection measures, including beach nourishment, accompanied with groin system or multiple detached breakwaters were proposed to combat with beach erosion. The analysis presented in this study is helpful to understand the morphodynamics and to predict the future change of beaches.

Nutrient limitation of soil organic carbon stocks under straw return - Fei Mo; Dayang Yang; Xiukang Wang; Thomas W. Crowther; Nangia Vinay; Zhongkui Luo; Kailiang Yu; Shikun Sun; Feng Zhang; Youcai Xiong; Yuncheng Liao (Soil Biology and Biochemistry, 2024)

Including soil depth as a predictor variable increases prediction accuracy of SOC stocks - Jiaying Li; Feng Liu; Wenjiao Shi; Zhengping Du; Xiangzheng Deng; Yuxin Ma; Xiaoli Shi; Mo Zhang; Qiquan Li (Soil and Tillage Research, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Study on window-opening behavior of suburban sustainable life-pattern in residential buildings at Donglu town of Hezhou, China - Jie Han; Nan Mo; Jingyi Cai; Xinyue Li; Fuhao Xie; You Peng; Tao Feng (Journal of Cleaner Production, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Evidence for the smallest fossil Pongo in southern China - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jinyou Mo; Yuexing Feng; Wei Liao; Wei Wang (Journal of Human Evolution, 2024)

Corrigendum to “Integrated aerobic granular sludge and membrane process for enabling municipal wastewater treatment and reuse water production” [Chem. Eng. J. 337 (2018) 300–311] - Li Wang; Wenzhong Liang; Wensong Chen; Wenxiang Zhang; Jiahao Mo; Kaiguo Liang; Bing Tang; Yi Zheng; Feng Jiang (Chemical Engineering Journal, 2024)

Micro(nano)plastics in human urine: A surprising contrast between Chongqing's urban and rural regions - Xuan Song; Tian Chen; Zongwen Chen; Lixia Du; Xihong Qiu; Yuxin Zhang; Yan Li; Yu Zhu; Zhongyou Tan; Yunbo Mo; Xiaoqian Feng (Science of The Total Environment, 2024)

A holistic approach to projecting streamflow and analyzing changes in ecologically relevant hydrological indicators under climate and land use/cover change - Yang Liu; Feng Liu; Cheng Chen; Qiuwen Chen; Jianyun Zhang; Kangle Mo; Qinghu Jiang; Siyang Yao (Journal of Hydrology, 2024)

Activated DBP degradation and relevant signal transduction path via quorum sensing autoinducers in Streptomyces sp. SH5 - Ganxing Liu; Hao An; Lei Tang; Zhewei Chi; Yunwen Bi; Zeqi Ye; Haiming Zhao; Lei Xiang; Naixian Feng; Cehui Mo; Delin Xu (Journal of Hazardous Materials, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Oral-based nanoparticle-wrapped dsRNA delivery system: a promising approach for controlling an urban pest, Blattella germanica - Gui-Jun Long; Xuan-Zheng Liu; Huan Guo; Meng-Qi Zhang; Lang-Lang Gong; Yun-Feng Ma; Youssef Dewer; Wu-Jia Mo; Ling-Wen Ding; Qin Wang; Ming He; Peng He (Journal of Pest Science, 2024)

Performance and mechanism of biochar@FeMg-LDH for efficient activation of persulfate for degradation of 2, 4-dichlorophenol in groundwater - Yuanye Mo; Xianrong Meng; Chengbao Liu; Wei Xu; Leizhi Zheng; Feng Chen; Junchao Qian; Hui Cai; Zhigang Chen (Environmental Science and Pollution Research, 2024)

Evaluation of the fate of wastewater effluent organic matter in receiving water: Effect of sequential photochemical and biological processes - Lei Zheng; Feng Xiao; Xinyi Zhang; Yang Deng; Shansheng Mo; Zhongli Liu; Xin Gu; Norbert Hertkorn; Gregory V. Korshin; Mingquan Yan (Journal of Hazardous Materials, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Reductive roasting of red mud with carbon and sulfuric acid dissolution of iron and aluminum: Transformation phases and leaching characteristics - Yuhua Huang; Wei Mo; Jinpeng Feng; Rulong Ren; Wei Guo; Xiujuan Su; Jinlin Yang; Chunyan He (Hydrometallurgy, 2024)

Molecular and geochemical characteristics of lignite in different plant sources evaluated using unsupervised analyses - Yang-Yang Xu; Xing Fan; Feng-Yun Ma; Wen-Long Mo; Xiang Bai; Xian-Yong Wei; Peter N Kuznetsov (Fuel, 2024)

Effects of potassium sorbate on systemic inflammation and gut microbiota in normal mice: A comparison of continuous intake and washout period - Nanhai Xiao; Shengyue Ruan; Qiufen Mo; Minjie Zhao; Tao Liu; Fengqin Feng (Food and Chemical Toxicology, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Quaternary evolution of the Meiji Atoll (Mischief Reef) in the southern South China Sea - Feng Wu; Xinong Xie; Wen Yan; Youhua Zhu; Beichen Chen; Jianuo Chen; Mo Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Hirudin ameliorates myocardial ischemia–reperfusion injury in a rat model of hemorrhagic shock and resuscitation: roles of NLRP3-signaling pathway - Yang Bai; Jing Bai; Peng Lu; Yu-Mo Jing; Wei-Chao Zheng; Lu-Ying Wang; Jian-Hua Wang; Feng Wang (Molecular and Cellular Biochemistry, 2024)

Uncertainty quantification of CO 2 plume migration in highly channelized aquifers using probabilistic convolutional neural networks - Li Feng; Shaoxing Mo; Alexander Y. Sun; Jichun Wu; Xiaoqing Shi (Advances in Water Resources, 2024)

Improving storm surge simulations by considering wave-steepness-dependent drag coefficient in the northern East China Sea - Zhao Li; Shuiqing Li; Po Hu; Xingru Feng; Dongxue Mo; Jian Li (Ocean Modelling, 2023)

Corrigendum to “Artificial phylloplanes resembling physicochemical characteristics of selected fresh produce and their potential use in bacterial attachment/removal studies” [Food Control 149 (2023) 109730] - Sindy Palma-Salgado; Kang-Mo Ku; John A. Juvik; Thanh H. Nguyen; Hao Feng (Food Control, 2023)

Green and efficient utilization of beech sawdust waste for sorbitol production: Direct conversion residue via Ru2P/OMC derived from separated lignin - Longxin Liu; Mo Qiu; Huiling Zhang; Jingnan Yang; Feng Shen; Haixin Guo; Jirui Yang; Qingxin Guan; Wei Li (Chemical Engineering Journal, 2023)

The mediating effect of financial development on CO2 emissions: An empirical study based on provincial panel data in China - Feng Xiong; Rui Zhang; Huidong Mo (Science of The Total Environment, 2023)

Excellent adsorption properties of Mg/Al/Fe LDOs for Cr(VI) in water - Wei Mo; Yang Yang; Chunyan He; Yuhua Huang; Jinpeng Feng (Journal of Environmental Chemical Engineering, 2023)

Tough, multifunctional, and green double-network binary solvent eutectogel with in-situ generation of lignin nanoparticles based on one-step dual phase separations for wearable flexible strain sensors - Jisheng Yang; Yawen Feng; Bingzhen Wang; Jianshuo Miao; Shihai Wei; Han Li; Liuting Mo; Zhiyong Qin (Chemical Engineering Journal, 2023)

Spatial variation in the community structure and response of benthic macroinvertebrates to multiple environmental factors in mountain rivers - Zaoli Yang; Shufeng He; Tao Feng; Yuqing Lin; Mo Chen; Qinyuan Li; Qiuwen Chen (Journal of Environmental Management, 2023)

Low-dose benzo[a]pyrene exposure induces hepatic lipid deposition through LCMT1/PP2Ac-mediated autophagy inhibition - Yunqing Li; NingJing Liang; Tingting Tang; Zhijian Zheng; Muting Chen; Jiao Mo; Ning Zhang; Simi Liao; Yu Lei; Yijie Wu; Chunhua Lan; Huan Ding; et al. (Food and Chemical Toxicology, 2023)

Dynamic structure transformation of char precursors during co-pyrolysis of coal and HDPE by using ReaxFF MD simulation and experiments - Wei Feng; Mo Zheng; Jin Bai; Xianxian Zhang; Chuang Wu; Zhenxing Guo; Lingxue Kong; Zongqing Bai; Wen Li (Chemical Engineering Journal, 2023)

Genesis and controlling factors of Cenozoic dolostones in the South China Sea: a case study from core Nanke-1 in the Nansha Islands - Mo Zhou; Feng Wu; Xinong Xie; Wen Yan (Marine Geophysical Research, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Void fraction research and destructive examination of CFETR toroidal field coil protype joints - Yue Xu; Kun Lu; Guang Shen; Bing Hu; Feng Cheng; Chao Mo; Mengyuan Zhang; Yanyu Xie (Annals of Nuclear Energy, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Antibiotic resistance genes are closely linked with bacterial functions during anoxic-oxic treatment process of pig wastewater - Feng Huang; Chunhao Mo; Ze Cao; Yanli Pang; Yiwen Yang; Xindi Liao (Journal of Water Process Engineering, 2023)

Artificial phylloplanes resembling physicochemical characteristics of selected fresh produce and their potential use in bacterial attachment/removal studies - Sindy Palma-Salgado; Kang-Mo Ku; John A. Juvik; Thanh H. Nguyen; Hao Feng (Food Control, 2023)

Bimetallic ordered mesoporous carbon from lignin for catalytic selective hydrogenation of levulinic acid to γ-valerolactone - Xiaoqi Wang; Xinhua Qi; Mo Qiu; Feng Shen; Jirui Yang; Boxiong Shen (Fuel, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Model for predicting the hydraulic elements of drip irrigation system with automatic flushing valves under high sediment water - Hao Gao; Yan Mo; Jiandong Wang; Feng Wu; Ni Gao; Shihong Gong (Biosystems Engineering, 2023)

High-efficiency removal of Cs (I) by vermiculite/zinc hexacyanoferrate (II) composite from aqueous solutions - Tianya Dai; Jinpeng Feng; Jiann-Yang Hwang; Yangyang Bao; Chenhui Gao; Zeping Wang; Wei Mo; Xiujuan Su; Hongfei Lin (Journal of Environmental Chemical Engineering, 2023)

Elevated ozone enhances the network stability of rhizospheric bacteria rather than fungi - Zhengsheng Yu; Xin Chen; Feng Hua Zhai; Qun Gao; Xun Wen Chen; Xue Guo; Yansen Xu; Meng Ying Gao; Cehui Mo; Zhaozhong Feng; Yunfeng Yang; Hui Li (Agriculture, Ecosystems & Environment, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Genome mining-guided activation of two silenced tandem genes in Raoultella ornithinolytica XF201 for complete biodegradation of phthalate acid esters - Nai-Xian Feng; Fei Zhang; Yunchang Xie; Hui Bin; Lei Xiang; Yan-Wen Li; Fantao Zhang; Yunhong Huang; Hai-Ming Zhao; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Science of The Total Environment, 2023)

Response of partial nitritation/anammox granules to biodegradable organic input in bacterial community and functions - Feiyue Qian; Yaru Liu; Chenyun Mo; Huan Zhang; Feng Yan; Junjun Gao; Jinlong Zhuang (Journal of Water Process Engineering, 2023)

Improved estimation of vegetation water content and its impact on L-band soil moisture retrieval over cropland - Sijia Feng; Jianxiu Qiu; Wade T. Crow; Xingguo Mo; Suxia Liu; Sheng Wang; Lun Gao; Xinghan Wang; Shuisen Chen (Journal of Hydrology, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

Co-pyrolysis behaviors of coal and polyethylene by combining in-situ Py-TOF-MS and reactive molecular dynamics - Wei Feng; Mo Zheng; Lijun Jin; Jin Bai; Lingxue Kong; Huaizhu Li; Zongqing Bai; Wen Li (Fuel, 2023)

Seeking and identifying time window of antibiotic treatment under in vivo guidance of PbS QDs clustered microspheres based NIR-II fluorescence imaging - Sijia Feng; Mo Chen; Yuzhou Chen; Liman Sai; Shixian Dong; Huizhu Li; Yimeng Yang; Jian Zhang; Xing Yang; Xiaogang Xu; Yuefeng Hao; Amr Mohamed Khair Hussein Abdou; et al. (Chemical Engineering Journal, 2023)

Design and Evaluation of a Machine Integrating Ridge-Breaking, Fertilizing, and Ridging for Ratoon Sugarcane Without Intertillage - Shang-Ping Li; Jia-Feng Pan; Jia-Qin Zhong; Wei Li; De-Quan Yang; Qing-Gui Mo (Sugar Tech, 2022)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Electromagnetic induction effects on electrical activity within a memristive Wilson neuron model - Quan Xu; Zhutao Ju; Shoukui Ding; Chengtao Feng; Mo Chen; Bocheng Bao (Cognitive Neurodynamics, 2022)

Effects of polycyclic aromatic hydrocarbons fluoranthene on the soil aggregate stability and the possible underlying mechanism - Jixian Mo; Jingyi Feng; Wanying He; Yuze Liu; Ning Cao; Yu Tang; Siyu Gu (Environmental Science and Pollution Research, 2022)

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Potassium phosphite enhanced the suppressive capacity of the soil microbiome against the tomato pathogen Ralstonia solanacearum - Lv Su; Haichao Feng; Xingxia Mo; Juan Sun; Pengfei Qiu; Yunpeng Liu; Ruifu Zhang; Eiko E. Kuramae; Biao Shen; Qirong Shen (Biology and Fertility of Soils, 2022)

Prediction of Significant Wave Height in Offshore China Based on the Machine Learning Method - Zhijie Feng; Po Hu; Shuiqing Li; Dongxue Mo (Journal of Marine Science and Engineering, 2022)
Accurate wave prediction can help avoid disasters. In this study, the significant wave height (SWH) prediction performances of the recurrent neural network (RNN), long short-term memory network (LSTM), and gated recurrent unit network (GRU) were compared. The 10 m u-component of wind (U10), 10 m v-component of wind (V10), and SWH of the previous 24 h were used as input parameters to predict the SWHs of the future 1, 3, 6, 12, and 24 h. The SWH prediction model was established at three different sites located in the Bohai Sea, the East China Sea, and the South China Sea, separately. The experimental results show that the performance of LSTM and GRU networks based on the gating mechanism was better than that of traditional RNNs, and the performances of the LSTM and GRU networks were comparable. The EMD method was found to be useful in the improvement of the LSTM network to forecast the significant wave heights of 12 and 24 h.

The role of T-LAK cell-originated protein kinase in targeted cancer therapy - Lu Zhang; Fei Wang; Huijun Yi; Svetlana P. Ermakova; Olesya S. Malyarenko; Jianmei Mo; Yingze Huang; Qiuhong Duan; Juanjuan Xiao; Feng Zhu (Molecular and Cellular Biochemistry, 2022)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Resting-State MEG Source Space Network Metrics Associated with the Duration of Temporal Lobe Epilepsy - Junpeng Zhang; Jingwen Feng; Yifan Zhang; Site Mo; Jingjing Dong; Haitao Zhu; Ling Zhang; Ting Wu; Yuan Cui; Duo Chen (Brain Topography, 2021)

Causal Relationship Between Complement C3, C4, and Nonalcoholic Fatty Liver Disease: Bidirectional Mendelian Randomization Analysis - Longman Li; Lulu Huang; Aimin Yang; Xiuming Feng; Zengnan Mo; Haiying Zhang; Xiaobo Yang (Phenomics, 2021)

Increasing mortality caused by chronic obstructive pulmonary disease (COPD) in relation with exposure to ambient fine particulate matters: an analysis in Southeastern China - Zhijian Chen; Qiuli Fu; Guangming Mao; Lizhi Wu; Peiwei Xu; Dandan Xu; Zhifang Wang; Xuejiao Pan; Yuan Chen; Xiaoming Lou; Zhe Mo; Xiaofeng Wang; et al. (Environmental Science and Pollution Research, 2021)

Distribution and Exposure Risk Assessment of Perfluorinated Alkyl Substances in Aquatic Products along the Coastal Region of the South China Sea - Xu-Feng Wang; Meng-Song Mo; Hai-Gang Chen; Qiang Wang; Jin-Lan Yang; Dong-Hao Zhao (Exposure and Health, 2021)

Hydrogeological modelling to support urban planning in harbour areas: a case study from Horsens, Denmark - Xinyu Cen; Anna Bondo Medhus; Theis Raaschou Andersen; Søren Erbs Poulsen; Mo Xu; Zishen Mou; Feng Du (Bulletin of Engineering Geology and the Environment, 2021)

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Associations Between Serum Multiple Metals Exposures and Metabolic Syndrome: a Longitudinal Cohort Study - Xiuming Feng; Longman Li; Lulu Huang; Haiying Zhang; Zengnan Mo; Xiaobo Yang (Biological Trace Element Research, 2021)

Analysis of Treatment Outcome After Endovascular Treatment in Different Pathological Subtypes of Basilar Artery Occlusion: a Single Center Experience - Xuan Sun; Raynald; Xu Tong; Feng Gao; Yiming Deng; Gaoting Ma; Ning Ma; Dapeng Mo; Ligang Song; Lian Liu; Xiaochuan Huo; Zhongrong Miao (Translational Stroke Research, 2021)

Travel Behaviours of Sharing Bicycles in the Central Urban Area Based on Geographically Weighted Regression: The Case of Guangzhou, China - Zongcai Wei; Feng Zhen; Haitong Mo; Shuqing Wei; Danli Peng; Yuling Zhang (Chinese Geographical Science, 2021)

LncRNA SNHG7 sponges miR-449a to promote pituitary adenomas progression - Xiongfei Yue; Ce Dong; Zhanying Ye; Lin Zhu; Xiaoyang Zhang; Xiaoyan Wang; Feng Mo; Zheng Li; Baogen Pan (Metabolic Brain Disease, 2021)

Nitrogen Regulates the Grain Yield, Antioxidant Attributes, and Nitrogen Metabolism in Fragrant Rice Grown Under Lead-Contaminated Soil - Huoyi Feng; Yuzhan Li; Yangfan Yan; Xinhang Wei; Yihan Yang; Long Zhang; Lin Ma; Wu Li; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2020)

Direct and indirect effects of microplastics on bivalves, with a focus on edible species: A mini-review - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ka Yan Man; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Silencing of Long Non-coding RNA GAS5 Suppresses Neuron Cell Apoptosis and Nerve Injury in Ischemic Stroke Through Inhibiting DNMT3B-Dependent MAP4K4 Methylation - Yiming Deng; Duanduan Chen; Feng Gao; Hong Lv; Guojun Zhang; Xuan Sun; Lian Liu; Dapeng Mo; Ning Ma; Ligang Song; Xiaochuan Huo; Tianyi Yan; et al. (Translational Stroke Research, 2020)

Application of Spirulina in aquaculture: a review on wastewater treatment and fish growth - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Reviews in Aquaculture, 2020)
There is an urgent need to find alternatives to fish meal and fish oil in compound feeds due to their rapidly rising prices and the demand for sustainable fisheries. Spirulina, a filamentous blue‐green microalga, is an excellent source of plant protein and could replace expensive animal‐derived proteins in fish feed. Studies have evaluated the use of spirulina as a fish meal for different fish species. This paper reviews research on the effects of spirulina on the growth performance of various fish species. It is apparent that spirulina can be a highly important component of the diet of fish; it has a number of benefits, such as promoting the growth of tilapia ( Oreochromis niloticus ) and carp ( Labeo rohita ), improving the reproductive performance of yellow tail cichlid ( Pseudotropheus acei ) and enhancing the immune response of rainbow trout ( Oncorhynchus mykiss ). Recent studies have shown that spirulina can be used for treating wastewater, including effluent from fish culture activities, as it can efficiently metabolize the nutrients and remove the heavy metals contained in aquaculture effluent. Fish aquaculture could apply an integrated strategy of simultaneously treating aquaculture effluent while producing spirulina biomass to supplement fish diets.

Succession of bacterial community and methanotrophy during lake shrinkage - Yongliang Mo; Feng Jin; Yan Zheng; Taogetao Baoyin; Adrian Ho; Zhongjun Jia (Journal of Soils and Sediments, 2020)

Response of Dendrobium officinale Kimura et Migo, a Prized Medicinal Plant, to Continuous UV-B Irradiation at Different C/N Ratios - Dandan Cui; Yuncai Mo; Lingjie Zeng; Kai Feng; Xiaoyun Feng; Jialing Huang; Mengling He; Xiaoyuan Zhang; Xifeng Teng (Journal of Plant Growth Regulation, 2020)

Identification of Sugarcane with NDVI Time Series Based on HJ-1 CCD and MODIS Fusion - Yanli Chen; Liping Feng; Jianfei Mo; Weihua Mo; Meihua Ding; Zhiping Liu (Journal of the Indian Society of Remote Sensing, 2020)
It is currently difficult to acquire the clear-sky data with high spatial resolutions in spring and summer in the southern region of China, making it impossible to carry out timely and fine monitoring of sugarcane planting information. Thus, Fusui, a sugarcane producing county in Guangxi, was selected in this paper to analyze the NDVI characteristics and change rules during the whole growth period of sugarcane based on MODIS and HJ-1 CCD remote sensing data, which were fused into 30 m resolution NDVI time series data with high accuracy by using the spatial and temporal fusion model of multi-source remote sensing data ESTRAFM. In addition, the NDVI change rate and sample automatic training threshold were used to construct the sugarcane planting information identification model. The results showed that the fused images showed a high similarity with the observed images, indicating good fusion quality. Moreover, the correlation coefficients in the sugarcane planting area reached 0.953, and AD, AAD and SD were 0.033, 0.019 and 0.007, respectively. The NDVI change rate model was used to identify the sugarcane planting information in different time phases of 113 d, 129 d, 145 d, 193 d and 209 d in spring and summer, and the overall accuracy was 92.17%, 92.58%, 91.78%, 90.52% and 91.17%, respectively. The established model also achieved good results in 2017 with the overall accuracies are 88.44%, 87.79%, 89.79%, 88.34% for 113 d, 145 d, 193 d and 209 d.

Comprehensive transcriptome analysis of faba bean in response to vernalization - Bei Gao; Xiao-Chun Bian; Feng Yang; Mo-Xian Chen; Debatosh Das; Xiu-Ru Zhu; Yong Jiang; Jianhua Zhang; Yun-Ying Cao; Chun-Fang Wu (Planta, 2020)

Water-assisted synthesis of shape-specific BiOCl nanoflowers with enhanced adsorption and photosensitized degradation of rhodamine B - Xianlong Zhang; Long Yuan; Fengbing Liang; Dong An; Zhen Chen; Dexin Feng; Mo Xian (Environmental Chemistry Letters, 2020)

The Rpf84 gene, encoding a ribosomal large subunit protein, RPL22, regulates symbiotic nodulation in Robinia pseudoacacia - Zhao Feng; Lu Zhang; Yuanyuan Wu; Li Wang; Mingying Xu; Mo Yang; Yajuan Li; Gehong Wei; Minxia Chou (Planta, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

First report of sheath rot caused by Fusarium proliferatum on Pisang Awak Banana (Musa ABB) in China - Sui-Ping Huang; Ji-Guang Wei; Tang-Xun Guo; Qi-Li Li; Li-Hua Tang; Jian-You Mo; Ji-Feng Wei; Xiao-Bing Yang (Journal of Plant Pathology, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Effect of an incremental change in external water pressure on tunnel lining: a case study from the Tongxi karst tunnel - Yang Liu; Yongneng Feng; Mo Xu; Yunhui Zhang; Haitao Long; Haiming Zhu (Natural Hazards, 2019)

Influence of loading rate on strainburst: an experimental study - Guoshao Su; Jianqing Jiang; Xiating Feng; Quan Jiang; Zhiyong Chen; Jinhai Mo (Bulletin of Engineering Geology and the Environment, 2019)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Detection of lncRNA-mRNA interaction modules by integrating eQTL with weighted gene co-expression network analysis - Xing-Bo Mo; Long-Fei Wu; Xin Lu; Xiao-Wei Zhu; Wei Xia; Lan Wang; Pei He; Peng-Fei Bing; Yong-Hong Zhang; Fei-Yan Deng; Shu-Feng Lei (Functional & Integrative Genomics, 2019)

Nitrogen-doped porous carbon derived from chitosan for the enhanced dehydrochlorination of lindane under mild conditions - Jirui Yang; Feng Shen; Mo Qiu; Xinhua Qi (Environmental Science and Pollution Research, 2018)

Role of AMPK in atherosclerosis via autophagy regulation - Hanxiao Ou; Chuhao Liu; Wenjie Feng; Xinwen Xiao; Shengsong Tang; Zhongcheng Mo (Science China Life Sciences, 2018)

The triggering receptor expressed by myeloid cells-1 activates TLR4-MyD88-NF-κB-dependent signaling to aggravate ventilation-induced lung inflammation and injury in mice - Xiaoxia Wang; Bijun Luo; Yanyan Lu; Dengge Pang; Jianqiu Zheng; Jianlan Mo; Hui Huang; Jifeng Feng (Cell and Tissue Research, 2018)

Exposure to intermittent hypoxia impairs learning and memory ability in rats - Feng Zhang; Zhuo Tian; Sufen Peng; Jie Li; Xiang Yang; Hailan Mo; Jian Tan; Hongbing Yao; Bing Li (Sleep and Biological Rhythms, 2018)

Regional Characteristics of Typhoon-Induced Ocean Eddies in the East China Sea - Jianhong Wang; Meiqi Li; X. San Liang; Xing Wang; Feng Xue; Mo Peng; Chunsheng Miao (Advances in Atmospheric Sciences, 2018)

Analysis of the impact of heat on new camellias using nondestructive methods - Y. L. Zhang; W. Z. Guo; X. P. Li; F. Luo; J. B. Mo; S. C. Feng (Acta Physiologiae Plantarum, 2018)

Polycyclic aromatic hydrocarbons in farmland soils around main reservoirs of Jilin Province, China: occurrence, sources and potential human health risk - Yanan Chen; Jiquan Zhang; Feng Zhang; Fengxu Li; Mo Zhou (Environmental Geochemistry and Health, 2018)

Attraction behaviour of Anagrus nilaparvatae to remote lemongrass ( Cymbopogon distans ) oil and its volatile compounds - Guo-Feng Mao; Xiao-Chang Mo; Hatem Fouad; Ghulam Abbas; Jian-Chu Mo (Natural Product Research, 2018)

The distribution and functional relevance analysis of runs of homozygosity (ROHs) in Chinese Han female population - Yi-Hua Lu; Bing-Hua Wang; Wei Xia; Xing-Bo Mo; Long-Fei Wu; Xiao-Wei Zhu; Pei He; Fang-Fei Xie; Xin Lu; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Petrogensis and tectonic setting of the Y emaquan granite from the iron‐polymetallic ore area of Q imantag, E astern K unlun M ountains, Qinghai–Tibet P lateau - Aikui Zhang; Xuanxue Mo; Wanming Yuan; Nimat U. Khattak; Chengyou Feng; Wenquan Zhang; Guanglian Liu; Xiangyang Jing; Nana Hao (Island Arc, 2017)
Being a part of the P aleo‐ T ethys O cean, closing of the B uqingshan‐ A nyemaqen oceanic basin left a rich geologic record in the E ast K unlun O rogenic B elt. The genesis and tectonic setting of the granites including quartz monzodiorite, granodiorite and mozogranite is discussed in light of the geochemical and U – P b chronological data obtained. U – P b dating studies on zircon from the quartz monzodiorite and monzogranite of the research area yielded ages of 220.11 ± 0.49 M a ( (Mean Square Weighted Deviates) MSWD = 0.046) and 223.33 ± 0.54 M a ( MSWD = 0.14), respectively, by Laser Ablation Multiple Collector Inductively Coupled Plasma Mass Spectrometry ( LA–MC–ICP–MS ) method. According to sedimentological and structural investigations, the P aleo‐ T ethys O cean in the Q imantag region began to close at about 235 M a, and completely disapperared at about 220 M a. The three types of granites in this study are considered to intrude the syn‐ to post‐collisional stages. The quartz monzodiorite and granodiorite belong to the I ‐type granite whereas the monzogranite is of the S ‐type granite. These two types of granites were formed by different ways of partial melting: first, partial melting of the lower crust took place as a result of asthenosphere upwelling triggered by break‐up of the leading edge or tearing of the descending oceanic slab. Subsequently partial melting of the middle–lower crust was caused by the underplating of basaltic magma formed by partial melting of the mantle wedge fluxed by fluids liberated by the oceanic slab dehydration. The magma responsible for the formation of S ‐type granites appears to have originated from partial melting of the upper crustal material at a shallower level with a clear signature of continental crust.

Contrasting impacts of two subtropical earthworm species on leaf litter carbon sequestration into soil aggregates - Jingtao Wu; Hanqing Li; Weixin Zhang; Feng Li; Jinhua Huang; Qifeng Mo; Hanping Xia (Journal of Soils and Sediments, 2017)

Effects of Glycyrrhetinic Acid on GSH Synthesis Induced by Realgar in the Mouse Hippocampus: Involvement of System X AG - $$ X_{AG^{-}} $$ , System X C - $$ X_{C^{-}} $$ , MRP-1, and Nrf2 - Yan-lei Wang; Mo Chen; Tao-guang Huo; Ying-hua Zhang; Ying Fang; Cong Feng; Shou-yun Wang; Hong Jiang (Molecular Neurobiology, 2017)

Interactions between selenite and different forms of antimony and their effects on root morphology of paddy rice - Qianhua Wu; Renwei Feng; Junkang Guo; Ruigang Wang; Yingming Xu; Zhilian Fan; Liangyu Mo (Plant and Soil, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Oral bioaccessibility and human exposure assessment of cadmium and lead in market vegetables in the Pearl River Delta, South China - Ping Zhuang; Yingwen Li; Bi Zou; Feng Su; Chaosheng Zhang; Hui Mo; Zhian Li (Environmental Science and Pollution Research, 2016)

Distribution and fractionation of cadmium in soil aggregates affected by earthworms (Eisenia fetida) and manure compost - Jingtao Wu; Hanqing Li; Feng Li; Yanju Zhang; Huanping Lu; Ping Zhuang; Qifeng Mo; Zhian Li (Journal of Soils and Sediments, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Genetic polymorphisms and DNA methylation in exon 1 CpG-rich regions of PACAP gene and its effect on mRNA expression and growth traits in half smooth tongue sole (Cynoglossus semilaevis) - Yufeng Si; Feng He; Haishen Wen; Jifang Li; Junli Zhao; Yuanyuan Ren; Meilin Zhao; Liqin Ji; Zhengju Huang; Mo Zhang; Songlin Chen (Fish Physiology and Biochemistry, 2016)

Biodegradation of di-n-butylphthalate and phthalic acid by a novel Providencia sp. 2D and its stimulation in a compost-amended soil - Hai-Ming Zhao; Huan Du; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo (Biology and Fertility of Soils, 2016)

Evolution process of the Late Silurian–Late Devonian tectonic environment in Qimantagh in the western portion of east Kunlun, China: Evidence from the geochronology and geochemistry of granitoids - NANA HAO; WANMING YUAN; AIKUI ZHANG; YUNLEI FENG; JIANHUI CAO; XIAONING CHEN; XUEQIN CHENG; XUANXUE MO (Journal of Earth System Science, 2015)

17β-Estradiol Ameliorates Light-Induced Retinal Damage in Sprague–Dawley Rats by Reducing Oxidative Stress - Shaolan Wang; Baoying Wang; Yan Feng; Mingshu Mo; Fangying Du; Hongbo Li; Xiaorui Yu (Journal of Molecular Neuroscience, 2015)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

The protective roles of S-adenosylmethionine decarboxylase (SAMDC) gene in melon resistance to powdery mildew infection - Changming Liu; Xiaoling Li; Ruiping Yang; Yanling Mo; Yongqi Wang; Feng Xian; Xian Zhang; Fei Wang (Horticulture, Environment, and Biotechnology, 2014)

Metabolic engineering of Escherichia coli for poly(3-hydroxypropionate) production from glycerol and glucose - Qi Wang; Peng Yang; Mo Xian; Lu Feng; Jiming Wang; Guang Zhao (Biotechnology Letters, 2014)

MicroRNAs Expression and Function in Cerebral Ischemia Reperfusion Injury - Yu Di; Yang Lei; Feng Yu; Fan Changfeng; Wang Song; Mo Xuming (Journal of Molecular Neuroscience, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

EPO-Dependent Activation of PI3K/Akt/FoxO3a Signalling Mediates Neuroprotection in In Vitro and In Vivo Models of Parkinson’s Disease - Yu Jia; Shi-Jing Mo; Qi-Qi Feng; Ma-Li Zhan; Li-Si OuYang; Jia-Chang Chen; Yu-Xin Ma; Jia-Jia Wu; Wan-Long Lei (Journal of Molecular Neuroscience, 2014)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

17β-Estradiol Impedes Bax-Involved Mitochondrial Apoptosis of Retinal Nerve Cells Induced by Oxidative Damage via the Phosphatidylinositol 3-Kinase/Akt Signal Pathway - Hongbo Li; Baoying Wang; Chunhui Zhu; Yan Feng; Shaolan Wang; Muhammad Shahzad; Chenghu Hu; Mingshu Mo; Fangying Du; Xiaorui Yu (Journal of Molecular Neuroscience, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Climate warming-induced upward shift of Moso bamboo population on Tianmu Mountain, China - Xin-zhang Song; Chang-hui Peng; Guo-mo Zhou; Hong Jiang; Wei-feng Wang; Wen-hua Xiang (Journal of Mountain Science, 2013)

Identification of non-TAL effectors in Xanthomonas oryzae pv. oryzae Chinese strain 13751 and analysis of their role in the bacterial virulence - Shuai Zhao; Wei-Lan Mo; Fan Wu; Wei Tang; Ji-Liang Tang; Boris Szurek; Valérie Verdier; Ralf Koebnik; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Association of RANTES and MBL gene polymorphisms with systemic lupus erythematosus: a meta-analysis - Wang-Dong Xu; Hui Peng; Mo Zhou; Min Zhang; Bao-Zhu Li; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Assessing Taiwan’s energy security under climate change - Shih-Mo Lin; Jun-Chiang Feng; Fu-Kuang Ko (Natural Hazards, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Identification of Cellulase Genes from the Metagenomes of Compost Soils and Functional Characterization of One Novel Endoglucanase - Hao Pang; Peng Zhang; Cheng-Jie Duan; Xin-Chun Mo; Ji-Liang Tang; Jia-Xun Feng (Current Microbiology, 2009)